GAMBAR ILUSTRASI BUKU CERITA ANAK â ANAK SEBAGAI PELESTARIAN DAN PENGEMBANGAN BUDAYA DI ERA GLOBALISASI - ., Kristanto . (MALIH PEDDAS, 2011)
GAMBAR ILUSTRASI BUKU CERITA ANAK â ANAK SEBAGAI PELESTARIAN DAN PENGEMBANGAN BUDAYA DI ERA GLOBALISASI Abstrak Rapidly changing time is make responsive teaching methods should be increasingly innovative. Its also a push for the educators to be vigilant in the face of understanding the value - the value as opposed to students and young people especially value - the value of arts and culture should prospectively be preserved and attached to the inspiration of future generations. The method is easily stimulated and responded to by the younger generation is through illustration, because it is visual, can be seen, komonikatif, informative and easy to understand. From an early age, children need to be equipped with a learning culture through childrens story books - children who are Illustrative as investment value - the value of culture in children - children who can protect themselves and respond to the challenges of globalization both present and future. Â